Current progress on the microbial therapies for acute liver failure - Huang, Jiayuan; Xu, Tianyu; Quan, Guoqiao; Li, Yuange; Yang, Xiaoya; Xie, Wenrui (Frontiers in Microbiology, 2024)
Acute liver failure (ALF), associated with a clinical fatality rate exceeding 80%, is characterized by severe liver damage resulting from various factors in the absence of pre-existing liver disease. The role of microbiota in the progression of diverse liver diseases, including ALF, has been increasingly recognized, with the interactions between the microbiota and the host significantly influencing both disease onset and progression. Despite growing interest in the microbiological aspects of ALF, comprehensive reviews remain limited. This review critically examines the mechanisms and efficacy of microbiota-based treatments for ALF, focusing on their role in prevention, treatment, and prognosis over the past decade.